Can India become an export platform for global operations of Japanese and American multinational corporations affiliates? - Nobuaki Yamashita (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2012)
This paper examines various indicators of the economic activities of Japanese and American multinational corporation (MNC) affiliates in India compared to the case of China, using the unique affiliate-level data. The study shows that Japanese MNCs in India follow the typical MNC expansion strategy in that rapidly growing emerging economy with a focus on the transport equipment industry, whereas United States counterparts are concentrated more in information technology-related services, thus strengthening service-led growth of the Indian economy. However, the author remains sceptical of the expectation that India will grow as an export platform similar to China because of the former country's unique FDI experiences and rising domestic market potential.
Keywords: F14; F23; O53; 330; production networks; multinational corporations; FDI; India; China; Multinationales Unternehmen; Ausländische Tochtergesellschaft; Japanisch; Amerikanisch; Indien; China